To (start with) Oop, or Not Oop : that is not the question* / Syed Ahmad Aljunid - Aljunid, Syed Ahmad (Fakulti Teknologi Maklumat dan Sains Kuantitatif, 2001)
Lately, in UiTM, there has been a hue and cry against starting programming course with object-oriented programming (OOP), and opting to get back to the procedural paradigm first. This paper is an attempt to dismiss these notions. It argues that the wrong question has been asked. That problem is trivial. Instead, the more pressing question is: "How, in the present state of rapidly changing and expanding IT field, can we effectively teach fundamental programming principles and computer problem solving methodology without clouding the students with syntax and nontransparent tools?" Another related question is "How can we make programming attractive to the new students?" Essentially, it is not the question of when, but how. And what too. In short, we should actually revise our programming pedagogy thoroughly as well as review our programming curriculum. We present our case based on the successful implementation of the minimalist cum black box cum 4-stage approaches in introducing OOP to beginners of programming in various institutions Our solution nevertheless takes into consideration our own background and constraints.